Impacto do videogame ativo sobre a ansiedade e depressão de adolescentes com excesso de peso: Ensaio clínico randomizado - Silva, Naryelle da Rocha (2019)
Overweight in childhood and adolescence, coupled with a sedentary lifestyle, has implications that go beyond physical aspects, but can have an impact on the mental health of individuals. The aim of this study was to evaluate the impact of active videogame, with the aid of gamification, on the anxiety and depression of adolescents with overweight or obesity. This was a randomized clinical trial conducted between February and June 2018. The sample consisted of 73 overweight or obese adolescents, divided into two groups (experimental and control), aged between 10 and 17 years, enrolled between the 5th and 9th years of elementary education in public schools in the city of Campina Grande - PB. Socioeconomic, demographic and lifestyle variables, as well as nutritional status (body mass index) and mental health (anxiety and depression) were studied. In order to perform the intervention, the XBOX 360 platform was used with the Kinect accessory (Microsoft®) to allow the user to control and interact only with command of the body movements, causing him to perform physical activity. A general form, the Beck Anxiety Inventory (BAI) and the Beck II Depression Inventory (BDI II) was applied, as well as the measurement of weight and height. In order to increase adolescents' engagement in the intervention activity, a gamification strategy was adopted and adolescent adherence was based on attendance at physical activity sessions as well as supervised activity. The chi-square test was applied to perform a comparative analysis between the socioeconomic and demographic characteristics, related to the style and nutritional status of the adolescents in the two comparison groups, in order to evaluate the randomization procedure. The same test was used to evaluate the effect of the inte rvention between the groups and, finally, the McNemar test was applied to evaluate the effect of intra - group intervention. SPSS version 22.0 was used and a significance level of 5% was adopted. The study was approved by the Ethics Committee in Research, CAAE: 84019518.3.0000.5187, was registered in Clinical Trials (NCT03532659) and REBEC (RBR- 2xn3g6). As a result, no statistically significant changes were observed in anxiety and depression levels before and after the intervention. In the experimental group, there was a decrease in the percentage of adolescents with moderate / severe depression after the intervention (57.9% to 52.9%), unlike the control group, where an increase was observed (42 , 1 for 47.1%), however these variations were not statistically significant. No changes were noted in the occurrence of anxiety and depression due to the proposed intervention. It is believed that longer periods of activity, as well as the association of psychological intervention, could bring better results.